(untitled) (KYAMC Journal, 2013)
Suicide is one of the forms of criminal offence in our country and it is also prevailing in other countries of the world. Whenever attempts to commite suicide and does any act towards the commission of such offence, shall be punished with simple imprisonment for a term which may extend to one year or with fine or with both. Shooting, hanging and stabbing are a ’hard way’ of committing suicide and typically a male choice. Poisoning and drowning are ’soft way’ of committing suicide and typically a female choice. A retro spective study was conducted on suicidal death, the department of forensic medicine, Dinajpur medical college. 20 cases were examined from June 2004 to June 2006 for 2 years. All the cases were referred from 13 different police stations and one railway station of Dinajpur district. Among them the highest number of cases were brought by Kotowally police station and the lowest from Hakimpur police station. But among the 20 cases 70% were female Muslims. The highest frequency of offence was found in lower socioeconomic growth. The age group of the was from 20 - 35 years. KYAMC Journal Vol. 3, No.-2, January 2013, Page 298-300 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15171